2004
DOI: 10.1023/b:phot.0000046153.08935.4c
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Nitrogen Deficiency on Gas Exchange, Chlorophyll Fluorescence, and Antioxidant Enzymes in Leaves of Rice Plants

Abstract: Gas exchange, chlorophyll (Chl) fluorescence, and contents of photosynthetic pigments, soluble proteins (ribulose-1,5bisphosphate carboxylase/oxygenase, RuBPCO), and antioxidant enzymes were characterized in the fully expanded 6 th leaves in rice seedlings grown on either complete (CK) or on nitrogen-deficient nutrient (N-deficiency) solutions during a 20-chase period. Compared with the control plants, the lower photosynthetic capacity at saturation irradiance (P max ) was accompanied by an increase in interce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
159
3
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(198 citation statements)
references
References 36 publications
29
159
3
1
Order By: Relevance
“…Furthermore, N deficiency can produce oxidative damage in illuminated cultures as reported for higher plants (38). Thus, carotenoid accumulation might be a biological response to induce oxidative damage.…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Furthermore, N deficiency can produce oxidative damage in illuminated cultures as reported for higher plants (38). Thus, carotenoid accumulation might be a biological response to induce oxidative damage.…”
Section: Resultsmentioning
confidence: 80%
“…It was shown that nitrogen deficiency affected the photosynthetic apparatus in leaves of rice plants, leading to lowered fluorescence parameters (photosynthetic yield, quantum yield for photosystem II, PSII, electron transport rate, and quenching) as well as lowered photosynthetic capacity at saturation irradiance, which are indicators of photoinhibition. In addition, the carotenoid-to-chlorophyll ratio increased and the activities of antioxidant enzymes were lowered, which led to aggravation of membrane lipid peroxidation (i.e., oxidative damage) (38).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nitrogen is also an important element in RuBisCO photosynthetic complexes, the Calvin-Benson cycle enzymes, chlorophyll, and carotenoids (Correia et al 2005). Nitrogen deficiency contributes to reductions in transpiration, stomatal conductance, the chlorophyll and carotenoids content, and the concentration of soluble sugars (Huang et al 2004). Insufficient nitrogen uptake also reduces the electron acceptor pool in PSII and decreases RuBisCO and phosphoenolpyruvate carboxylase (PEPCase) activity (Correia et al 2005).…”
Section: Nutrient Deficiency Stressmentioning
confidence: 99%
“…Lipid peroxidation was measured according to the experimental procedure of Huang et al (2004). First, 50 mg of thalli was rinsed in distilled water and homogenized in 0.1% trichloroacetic acid, and subsequently a small amount (1.5 mL) of homogenate was centrifuged.…”
Section: Membrane Lipid Peroxidationmentioning
confidence: 99%